1992
DOI: 10.1128/jb.174.1.155-160.1992
|View full text |Cite
|
Sign up to set email alerts
|

In vitro repair of double-strand breaks accompanied by recombination in bacteriophage T7 DNA

Abstract: A double-strand break in a bacteriophage T7 genome significantly reduced the ability of that DNA to produce viable phage when the DNA was incubated in an in vitro DNA replication and packaging system. When a homologous piece of T7 DNA (either a restriction fragment or T7 DNA cloned into a plasmid) that was by itself unable to form a complete phage was included in the reaction, the break was repaired to the extent that many more viable phage were produced. Moreover, repair could be completed even when a gap of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 43 publications
(52 reference statements)
1
22
0
Order By: Relevance
“…The yield of viable phage reflects the number of intact genomes and, therefore, the efficiency of double-strand break repair. Double-strand breaks are repaired efficiently in this system, and repair of the breaks is often accompanied by acquisition of genetic information from other DNA molecules present in the same reactions (25). When a double-strand break occurs between a pair of direct repeats, the break can increase the frequency of deletion of the region between the repeats by 2 or more orders of magnitude (13,55).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The yield of viable phage reflects the number of intact genomes and, therefore, the efficiency of double-strand break repair. Double-strand breaks are repaired efficiently in this system, and repair of the breaks is often accompanied by acquisition of genetic information from other DNA molecules present in the same reactions (25). When a double-strand break occurs between a pair of direct repeats, the break can increase the frequency of deletion of the region between the repeats by 2 or more orders of magnitude (13,55).…”
mentioning
confidence: 99%
“…A connection between double-strand breaks and recombination (both homologous and illegitimate) has been well established in a number of biological systems, including yeasts, bacteria, and bacteriophages (9,12,32,44,46,53,54). Our laboratory has been examining the repair of double-strand breaks by using an in vitro system based on extracts made from Escherichia coli infected with bacteriophage T7 (13,21,25,55). In this system, DNA replication closely mimics the in vivo replication of T7 DNA (4, 28).…”
mentioning
confidence: 99%
“…Recombination (2) and DNA repair (14,15) are extremely efficient in T7-infected cells even in the absence of the host RecA pathway (16). gp6 plays a critical role in recombination as evidenced by the absence of DNA exchange when E. coli is infected with bacteriophage T7 deficient in gp6; using density labeling, no hybrid T7 molecules are observed (17).…”
mentioning
confidence: 99%
“…We have proposed, on the basis of in vitro studies, that the efficient recombination observed in phageinfected cells is mediated by the T7 gene 2.5 protein and the T7 gene 4 helicase (2). Furthermore, recombinational repair of dsDNA breaks in T7 phage-infected cells is very efficient (15,16). The studies presented here show that the helicasemediated strand transfer reaction has the capability to play a major role in postreplication recombinational repair.…”
Section: Discussionmentioning
confidence: 81%
“…Recombination (14) and DNA repair (15,16) in E. coli cells infected with bacteriophage T7 are extremely efficient, and recombination is not impaired by the absence of the host RecA pathway (17). Consequently, we believe that the T7 gene 4 helicase-mediated strand exchange reaction provides the major pathway for recombination in E. coli cells infected with bacteriophage T7 (2).…”
mentioning
confidence: 99%